Increased body mass index makes an impact on brain white-matter integrity in adults with remitted first-episode mania. Issue 3 (26th April 2013) - Kuswanto, C. N.; Sum, M. Y.; Yang, G. L.; Nowinski, W. L.; McIntyre, R. S.; Sim, K.
Abstract : Background: Obesity is increasingly prevalent in bipolar disorder (BD) but data about the impact of elevated body mass index (BMI) on brain white-matter integrity in BD are sparse. Based on extant literature largely from structural magnetic resonance imaging (MRI) studies, we hypothesize that increased BMI is associated with decreased fractional anisotropy (FA) in the frontal, temporal, parietal and occipital brain regions early in the course of BD. Method: A total of 26 euthymic adults (12 normal weight and 14 overweight/obese) with remitted first-episode mania (FEM) and 28 controls (13 normal weight and 15 overweight/obese) matched for age, handedness and years of education underwent structural MRI and diffusion tensor imaging scans. Results: There are significant effects of diagnosis by BMI interactions observed especially in the right parietal lobe (adjusted F 1, 48 = 5.02, p = 0.030), occipital lobe (adjusted F 1, 48 = 10.30, p = 0.002) and temporal lobe (adjusted F 1, 48 = 7.92, p = 0.007). Specifically, decreased FA is found in the right parietal ( F 1, 23 = 5.864, p = 0.023) and occipital lobes ( F 1, 23 = 4.397, p = 0.047) within overweight/obese patients compared with normal-weight patients with FEM. Compared with overweight/obese controls, decreased FA is observed in right parietal ( F 1, 25 = 6.708, p = 0.015), temporal ( F 1, 25 = 10.751, p = 0.003) and occipital ( F 1, 25 = 9.531, p = 0.005) regions in overweight/obese patients with FEM. Conclusions: Our findings suggest that increased BMI affects temporo-parietal-occipital brain white-matter integrity in FEM. This highlights the need to further elucidate the relationship between obesity and other neural substrates (including subcortical changes) in BD which may clarify brain circuits subserving the association between obesity and clinical outcomes in BD.